Alpha-1 antagonist treatment for eyelid retraction in patients with thyroid eye disease-a prospective pilot study - Arnon, Roee; Goldberg, Hila; Ben-Simon, Guy J; Priel, Ayelet; Zloto, Ofira; Landau-Prat, Daphna; Cukierman-Yaffe, Tali; Agmon-Levin, Nancy; Sagiv, Oded (Eye (London), 2025)
Sympathetic overstimulation of Müller's muscle is a suggested mechanism underlying upper eyelid retraction in thyroid eye disease (TED). We examined the effect of tamsulosin, an alpha-1 antagonist, on eyelid retraction in patients with TED. A single-centre prospective study. Patients with TED and associated eyelid retraction were treated with oral 0.4 mg/day tamsulosin for 3 months. Upper eyelid margins-to-reflex distance (MRD1), vertical palpebral fissure height (PFH), subjective improvement, signs and symptoms of dry eye, and lubricants use were assessed at baseline and at each subsequent visit. Eleven suitable patients (mean age 47.5 ± 9.68, 8 females) enrolled in the study. Three patients discontinued the drug due to mild adverse effects (dizziness, bradycardia, nausea, and gastrointestinal distress), which resolved immediately upon stopping treatment. The other eight patients tolerated the drug well and reported no side effects. Five patients experienced an objective improvement in eyelid position and subjective improvement in eye discomfort. The mean MRD1 decreased by -1.04 ± 0.81 mm (P = 0.015), and mean PFH decreased by -1.46 ± 1.33 mm (P = 0.039). Mean duration of tamsulosin treatment was 84.63 ± 71.9 days. Patients discontinued the drug due to no improvement in MRD1 (n = 3), referral for eyelid surgery with stable inactive TED (n = 2), treatment with intravenous methylprednisolone due to worsening active TED (n = 2), and patient choice after 5 months of treatment with spontaneous resolution of symptoms (n = 1). Tamsulosin is a safe potential treatment for eyelid retraction in TED and can be used as a temporary alternative therapeutic approach for patients unsuitable for surgery.